2017
DOI: 10.1177/0022466917713983
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Mobile Technology Supporting Individuals With Disabilities

Abstract: Mobile technology has become ubiquitous in the education and support of individuals with disabilities. While this practice is supported under the Universal Design for Learning framework, research in the area has yet to establish a solid evidence base. The majority of the studies in existence are single-subject design studies with a dearth of replication to support their results, and many do not meet the Council for Exceptional Children’s Standards for Evidence-Based Practices in Special Education guidelines. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…A recent paper by Chmiliar and Anton (2017) provides insight into the uses of mobile technologies that students with disabilities wish to have: technologies to read syllabi and course content; apps to check, write and submit assignments, as well as apps to check grades, take a quiz, post to a discussion forum, read discussion forum posts, communicate with instructors and other students, and read the textbook. Despite the variety of articles discussing the features and uses of mobile apps and devices, Cumming and Rodrí guez (2017), in their meta-analysis of mobile tech supporting individuals with disabilities, concluded that, "research in the area has yet to establish a solid evidence base" (p 164).…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper by Chmiliar and Anton (2017) provides insight into the uses of mobile technologies that students with disabilities wish to have: technologies to read syllabi and course content; apps to check, write and submit assignments, as well as apps to check grades, take a quiz, post to a discussion forum, read discussion forum posts, communicate with instructors and other students, and read the textbook. Despite the variety of articles discussing the features and uses of mobile apps and devices, Cumming and Rodrí guez (2017), in their meta-analysis of mobile tech supporting individuals with disabilities, concluded that, "research in the area has yet to establish a solid evidence base" (p 164).…”
Section: Discussionmentioning
confidence: 99%
“…Cumming et al carried out a meta analysis on mobile technologies for the support of people with intellectual disabilities [23]. Their research was founded on a systematic literature review of single subject studies that used mobile technologies (smartphones, tablets, etc.)…”
Section: Related Workmentioning
confidence: 99%
“…Video modeling, task analysis, and technology-aided instruction and interventions are all recognized as evidence-based practices for youth with ASD (Wong et al, 2014). Much of the literature base investigating how to teach people to use mobile technologies (i.e., any handheld electronic computing devices such as a tablet, smartphone, and MP3 players) has outlined the use of video modeling, prompting, or a combination of both (Cumming & Drape Rodriguez, 2017; Kagohara, 2011; Kagohara et al, 2011; Kagohara et al, 2013; van der Meer et al, 2011). Only two studies exist that meet quality indicators (Council for Exceptional Children, 2014) for using an iPhone as a tool for people with disabilities and, although it did not meet quality indicators, there is only one study specifically where researchers investigate text messaging as a communication strategy for people with CCN (Cumming & Drape Rodriguez, 2017; Lancioni et al, 2012).…”
Section: Teaching Students To Use Mobile Technologiesmentioning
confidence: 99%
“…Although mobile technology is an exciting and relatively new communicative prospect for people with ASD, the technology and its accessibility are moving more rapidly than the ability to research the intricacies of using mobile devices as a common means for communication (McNaughton & Light, 2013; Rehabilitation Engineering Research Center on Communication Enhancement, 2011). Effective practices for teaching people with disabilities how to use the iPad and iPod for multiple purposes is an area that continues to be explored (Cumming & Drape Rodriguez, 2017). Much of the work in this area utilizes applied behavior analytic techniques to teach people with ASD and/or CCN how to use these devices (see Kagohara et al, 2013).…”
mentioning
confidence: 99%